Enabling Rapid Charging Lithium Metal Batteries via Surface Acoustic Wave‐Driven Electrolyte Flow. Issue 14 (18th February 2020) - Huang, An; Liu, Haodong; Manor, Ofer; Liu, Ping; Friend, James
Abstract: Both powerful and unstable, practical lithium metal batteries have remained a difficult challenge for over 50 years. With severe ion depletion gradients in the electrolyte during charging, they rapidly develop porosity, dendrites, and dead Li that cause poor performance and, all too often, spectacular failure. Remarkably, incorporating a small, 100 MHz surface acoustic wave device (SAW) solves this problem. Providing acoustic streaming electrolyte flow during charging, the device enables dense Li plating and avoids porosity and dendrites. SAW‐integrated Li cells can operate up to 6 mA cm −2 in a commercial carbonate‐based electrolyte; omitting the SAW leads to short circuiting at 2 mA cm −2 . The Li deposition is morphologically dendrite‐free and close to theoretical density when cycling with the SAW. With a 245 µm thick Li anode in a full Li||LFP (LiFePO4 ) cell, introducing the SAW increases the uncycled Li from 145 to 225 µm, decreasing Li consumption from 41% to only 8%. A closed‐form model is provided to explain the phenomena and serve as a design tool for integrating this chemistry‐agnostic approach into batteries whatever the chemistry within. Abstract : Remarkably, incorporating a small, 100 MHz surface acoustic wave device (SAW) makes rechargeable lithium metal batteries practical, avoiding dendrite growth and rapid failure by encouraging electrolyte flow, which in turn, eliminates the lithium depletion layer next to the anode, leading to dense lithium plating even during very rapid charging.